2021
DOI: 10.1371/journal.pone.0261127
|View full text |Cite
|
Sign up to set email alerts
|

Metformin attenuates osteoclast-mediated abnormal subchondral bone remodeling and alleviates osteoarthritis via AMPK/NF-κB/ERK signaling pathway

Abstract: This study explored the mechanism by which metformin (Met) inhibits osteoclast activation and determined its effects on osteoarthritis (OA) mice. Bone marrow-derived macrophages were isolated. Osteoclastogenesis was detected using tartrate-resistant acid phosphatase (TRAP) staining. Cell proliferation was evaluated using CCK-8, F-actin rings were detected by immunofluorescence staining, and bone resorption was detected using bone slices. Nuclear factor kappa-B (NF-κB) and nuclear factor of activated T-cell cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 43 publications
1
37
0
Order By: Relevance
“…In order to establish a mouse OA model, the right knee of mice was selected for DMM surgery [ 36 ]. Briefly, after mice were anesthetized with an intraperitoneal injection of 1% sodium pentobarbital (60 mg/kg) [ 37 ], the meniscotibial ligament of the right knee was transected to free the anterior crus of the meniscus, and sham surgery was performed without transecting the meniscotibial ligament. Mice were injected intra-articularly with Erastin (15 mg/kg) [ 38 ], and the sham and DMM groups were injected with an equal volume of saline twice a week.…”
Section: Methodsmentioning
confidence: 99%
“…In order to establish a mouse OA model, the right knee of mice was selected for DMM surgery [ 36 ]. Briefly, after mice were anesthetized with an intraperitoneal injection of 1% sodium pentobarbital (60 mg/kg) [ 37 ], the meniscotibial ligament of the right knee was transected to free the anterior crus of the meniscus, and sham surgery was performed without transecting the meniscotibial ligament. Mice were injected intra-articularly with Erastin (15 mg/kg) [ 38 ], and the sham and DMM groups were injected with an equal volume of saline twice a week.…”
Section: Methodsmentioning
confidence: 99%
“…Li et al [60] found that OPG levels were decreased, and RANKL levels were increased in subchondral bone of early OA in vivo. According to our previous study, the RANK/RANKL/OPG axis played a key role in the process of osteoclast activation in the subchondral bone of early OA [61,62].…”
Section: Discussionmentioning
confidence: 92%
“…A study has shown that AMP-activated protein kinase (AMPK) plays a negative regulatory role in osteoclast differentiation and function ( Tong et al, 2020 ). Multiple drugs can affect osteoclast differentiation and bone resorption through AMPK-mediated signaling pathways, such as AMPK/NF-κB/ERK, AMPK/mTOR/p70S6K, and AMPK/Nfr2 signaling pathways ( Li Z et al, 2018 ; Tong et al, 2018 ; Peng et al, 2019 ; Zhao et al, 2020 ; Guo et al, 2021 ). Unlike various other drugs whose effects on osteoclast differentiation and bone resorption through AMPK pathway have been widely studied, studies on how ZA affects osteoclasts through the AMPK pathway are relatively recent.…”
Section: Zoledronic Acid Inhibits Osteoclast Differentiationmentioning
confidence: 99%